IntraCoronary Artery Retrograde Thrombolysis vs. Thrombus Aspiration in ST-Segment Elevation Myocardial Infarction: Study Protocol for a Randomized Controlled Trial - Shen, Mingzhi; Wang, Jihang; Li, Dongyun; Zhou, Xinger; Guo, Yuting; Zhang, Wei; Guo, Yi; Wang, Jian; Liu, Jie; Zhao, Guang; Zhao, Shihao; Tian, Jinwen (Frontiers in Cardiovascular Medicine, 2022)
Background Type 2 diabetes (T2DM) is a major risk factor for myocardial infarction. Thrombus aspiration was considered a good way to deal with coronary thrombus in the treatment of acute myocardial infarction. However, recent studies have found that routine thrombus aspiration is not beneficial. This study is designed to investigate whether intracoronary artery retrograde thrombolysis (ICART) is more effective than thrombus aspiration or percutaneous transluminal coronary angioplasty (PTCA) in improving myocardial perfusion in patients with ST-segment elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PPCI). Methods/Design IntraCoronary Artery Retrograde Thrombolysis (ICART) vs. thrombus aspiration or PTCA in STEMI trial is a single-center, prospective, randomized open-label trial with blinded evaluation of endpoints. A total of 286 patients with STEMI undergoing PPCI are randomly assigned to two groups: ICART and thrombus aspiration or PTCA. The primary endpoint is the incidence of >70% ST-segment elevation resolution. Secondary outcomes include distal embolization, myocardial blush grade, thrombolysis in myocardial infarction (TIMI) flow grade, and in-hospital bleeding. Discussion The ICART trial is the first randomized clinical trial (RCT) to date to verify the effect of ICART vs. thrombus aspiration or PTCA on myocardial perfusion in patients with STEMI undergoing PPCI. Clinical Trial Registration [https://www.chictr.org.cn/], identifier [ChiCTR1900023849].